Mechanism of Oxidation of Ethane to Ethanol at Iron(IV)–Oxo Sites in Magnesium-Diluted Fe2(dobdc) - Verma, Pragya; Vogiatzis, Konstantinos D; Planas, Nora; Borycz, Joshua; Xiao, Dianne J; Long, Jeffrey R; Gagliardi, Laura; Truhlar, Donald G (Journal of the American Chemical Society, 2015)
The catalytic properties of the metal–organic framework Fe2(dobdc), containing open Fe(II) sites, include hydroxylation of phenol by pure Fe2(dobdc) and hydroxylation of ethane by its magnesium-diluted analogue, Fe0.1Mg1.9(dobdc). In earlier work, the latter reaction was proposed to occur through a redox mechanism involving the generation of an iron(IV)–oxo species, which is an intermediate that is also observed or postulated (depending on the case) in some heme and nonheme enzymes and their model complexes. In the present work, we present a detailed mechanism by which the catalytic material, Fe0.1Mg1.9(dobdc), activates the strong C–H bonds of ethane. Kohn–Sham density functional and multireference wave function calculations have been performed to characterize the electronic structure of key species. We show that the catalytic nonheme-Fe hydroxylation of the strong C–H bond of ethane proceeds by a quintet single-state σ-attack pathway after the formation of highly reactive iron–oxo intermediate. The mechanistic pathway involves three key transition states, with the highest activation barrier for the transfer of oxygen from N2O to the Fe(II) center. The uncatalyzed reaction, where nitrous oxide directly oxidizes ethane to ethanol is found to have an activation barrier of 280 kJ/mol, in contrast to 82 kJ/mol for the slowest step in the iron(IV)–oxo catalytic mechanism. The energetics of the C–H bond activation steps of ethane and methane are also compared. Dehydrogenation and dissociation pathways that can compete with the formation of ethanol were shown to involve higher barriers than the hydroxylation pathway.